Live Selling Produk Syariah oleh Influencer di TikTok : Tinjauan Fikih Muamalah dan Implikasinya terhadap Ekonomi Islam - Noor Alif Roihatul Jannah; Nia Mintarsih (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study observes how influencers sell sharia products through live selling on the TikTok platform and analyzes it from the perspective of muamalah fiqh and how it impacts the Islamic economy. This study shows that sharia-based direct selling can increase market access, expand the reach of sharia MSMEs, and encourage the development of a sharia-based digital economy. This can be seen from the transaction process and the sharia principles that must be adhered to. This study also emphasizes the importance of openness, honesty, and acceptance of contracts to ensure that the transactions carried out are halal and valid according to fiqh. Using a qualitative descriptive analysis methodology supported by literature and direct observation data, it was revealed that direct buying and selling practices can teach people the concept of Islamic economics and encourage ethical or sharia-compliant buying and selling behavior. However, violations of sharia principles such as marketing of illicit goods and fraudulent practices require ongoing supervision and training. This study shows that sharia live selling on TikTok can be an effective way to empower the people's economy and develop a sharia-based and ethical digital economic ecosystem.